2019
DOI: 10.1007/s00181-019-01684-7
|View full text |Cite
|
Sign up to set email alerts
|

The economic cost of the Arab Spring: the case of the Egyptian revolution

Abstract: This paper analyzes the effects that the Arab Spring and the subsequent revolution had on per capita real Gross Domestic Product in Egypt. The estimation procedure that we follow is the Synthetic Control Method. After comparing the observed evolution of Egyptian real output in the period 2011-2017 with that of synthetic Egypt, our estimates show i ) an accumulated loss in the growth rate of per capita real Gross Domestic Product of 12.04% (a yearly average of 1.56%); ii ) an accumulated loss in the per capita … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…In parallel, many studies (e.g. Khan, 2014; Prince et al , 2018; Echevarría and García-Enríquez, 2019) underline the adverse implications of the AS for Egypt's economy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel, many studies (e.g. Khan, 2014; Prince et al , 2018; Echevarría and García-Enríquez, 2019) underline the adverse implications of the AS for Egypt's economy.…”
Section: Resultsmentioning
confidence: 99%
“…These results could signify post-AS economic and political uncertainties that face entrepreneurship in Egypt. They could be indicative of some important implications for economic growth and for the business performance of the private sector, and they could be associated with the adverse economic implications of the AS (Khan, 2014; Prince et al , 2018; Echevarría and García-Enríquez, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Egypt's economy had been under severe strain since the revolution and has been subject to prolonged uncertainty and resource-constrained macroeconomic policies, all of which delayed responses to necessary stimulus packages, which adversely affected economic recovery in the wake of that revolution [59]. According to Echevarría and García-Enríquez [60] uncertainty during the years 2011-2017 resulted in reduced levels of domestic and foreign direct investment. They estimated a 1.6% loss in the annual growth rate of per capita real GDP, which amounted to a loss of USD 897 and an annual loss of USD 83.2 billion in the aggregate real GDP.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the per capita GDP was $9,857 in 2010 and fell to $9,814 by 2013. Furthermore, the investment to GDP ratio decreased from 19.5% in 2010 to 13.64% in 2014 (Echevarría and García-Enríquez, 2019). Abdelbaki (2013) showed that the Arab Spring produced economic and political instability in the Egyptian stock market.…”
Section: Research Settingmentioning
confidence: 99%